The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - Cigliano, John A.; Bauer, Amy; Draheim, Megan M.; Foley, Melissa M.; Lundquist, Carolyn J.; McCarthy, Julie-Beth; Patterson, Katheryn W.; Wright, Andrew J.; Parsons, E. C. M. (Frontiers in Marine Science, 2016)
Despite advances in marine conservation research, policy, and management, human activities continue to negatively affect marine species, habitats, and ecosystems, and the people who rely on them for needed resources. This begs the question: What is preventing us from being more effective in conserving marine species, habitats, and ecosystems? Answering this requires us to identify gaps in marine conservation efforts and develop a consensus on how best to target our efforts. One way to do this is to conduct research prioritization exercises. The questions discussed here were identified during a series of workshops designed to establish a list of important questions that need to be answered to advance marine conservation. We deemed these particular questions to be in a separate class than those considered in the associated paper “Seventy-One Important Questions for the Conservation of Marine Biodiversity” (Parsons et al., 2014b). These questions were put into a separate category because they were identified as areas of ecological, social, and economic research that include external drivers or required sizable paradigm shifts to address. Here we describe and discuss these “Kraken in the aquarium” questions—the marine equivalent of “the elephant in the room” questions—in four sections: human nature, meeting our responsibilities, entrenched interests, and corporate driven policy. Within each section, we address multiple questions by identifying the issues and offering examples of ways forward where possible. This paper is intended to start a dialog about these difficult questions that loom over marine conservation research and management. It is becoming increasingly important that the conservation practitioner community engages in these discussions and develops solutions in order for our work to be fully effective.